Strengthening Preservice Teachers Conceptual Understanding of Linear Algebra by Using the Supplementary Book Integrated with the GeoGebra and Maple Applications - Abdillah, Abdillah (Universitas Wiralodra, 2023)
Strengthening preservice teachers' understanding of the concept of Linear Algebra is a very important and necessary action. This study is a quasi-experiment. Therefore, the treatment was given to the experiment class in the form of The Supplementary Book integrated with the GeoGebra application and to the control class in the form of the Supplementary Book integrated with the Maple application. This study aims to find out the results of using the supplementary book integrated with the GeoGebra and Maple applications in strengthening the understanding of the concept of linear algebra. A sample of 50 preservice teachers from the Department of Mathematics Education at IAIN Ambon as the Experiment class and 45 preservice teachers from the Department of Mathematics Education at Darussalam University in Ambon as the control class. The research instrument consisted of pretest and posttest questions used to determine the results of strengthening the understanding of preservice teachers' linear algebra concepts and questionnaire instruments used for Intense Continuous Attitude.. The study was started by giving a pre-test, then giving treatment using a supplement book; after that, a post-test and giving a questionnaire were carried out. The average N-Gain Score for the experiment class (GeoGebra integration) was 0.80, while the control class (Maple 18 integration) was 0.78. Significance value Sig. (2-tailed) of 0.839, which indicates that there is no significant difference between the average value of the results of strengthening the ability to understand the concepts of the two classes.